Daring to lead: the psychodynamic relationship between anticipated image risk, leader-identity endorsement and leadership emergence in undergraduate student teams - Jordan, Emma (Organisational Psychology, 2025)
This study investigated some of factors that influence leadership emergence, despite potential image risks, in undergraduate student teams at a South African university. Data was collected for two studies. Both studies employed a quantitative research design to collect data through electronic, self-report surveys. The first study utilised cross-sectional data from students (N = 353) who had engaged in group work and assignments during their undergraduate career at university. The second study utilised a time-lagged design, in which second-year students (N = 27), who were engaged in group work for a 4-week period, were required to complete self- report surveys at two points in time – before team formation and after team assignment submission. Leader-identity endorsement and leadership emergence were found to be positively related in both Study 1 and Study 2. Anticipated image risk was found to be negatively related with both leader-identity endorsement and leadership emergence. Leader- identity endorsement mediated the relationship between anticipated image risk and leader- identity endorsement. Additionally, leadership self-efficacy mediated the relationship between anticipated image risk and leader-identity endorsement, as well as the relationship between anticipated image risk and leadership emergence. Theoretical and practical implications as well as recommendations for future research are presented.